PROBLEMATIKA MADRASAH DINIYAH (MD) DI KOTA PALOPO SULAWESI SELATAN PASCA OTONOMI DAERAH - Muhaemin, Muhaemin (INFERENSI, 2012)
AbstractThis research aims to map the opportunities of the Madrasah Diniyah inPalopo City, specially for institutional development context andanalyzing the challenges faced in realizing the ideal Madrasah Diniyahafter regional autonomy. This research is a qualitative descriptive. Ourcesof data are obtained from interviews, observation and documentation.Madrasah Diniyah development opportunities in Palopo supported bythe Center Education Qurâan that can be developed into a better madra-sah diniyah. Other opportunities dimension is the establishment of religionby the government of Palopo as the direction of development in Palopo.Challenges faced: first, the means and inadequate infrastructures. Secondly,there is no central figure. Third, public support is not maximized. Fourth,there has been no serious attention from the goverment. Fifth: the peoplehave felt confortableÂ  with the Center of Quran Education.AbstrakPenelitian ini bertujuan untuk memetakan peluang yang dimilikimadrasah diniyah di Kota Palopo, khususnya dalam konteks pengem-bangan kelembagaan dan menganalisis tantangan yang dihadapi dalammewujudkan madrasah diniyah yang ideal pasca otonomi daerah. Jenispenelitian ini adalah kualitatif deskriptif. Sumber data diperoleh dariwawancara, observasi dan dokumentasi. Peluang pengembangan lem-baga madrasah diniyah didukung oleh adanya sejumlah Taman Pen-didikan al-Qurâan (TPA) yang dapat dikembangkan menjadi madrasahdiniyah yang lebih baik. Selain itu, penetapan dimensi religi sebagaisalahsatu arah pembangunan Kota Palopo. Tantangan yang dihadapi,pertama: sarana dan prasarana tidak memakai. Kedua, tidak ada tokohpenggerak. Ketiga, dukungan masyarakat tidak signifikan. Keempat: tidak perhatian serius dari Pemerintah Kota. Kelima, masyarakat merasacukup dengan adanya TPA (Taman Pendidikan al-Qurâan)